2006
DOI: 10.1016/j.physa.2005.11.019
|View full text |Cite
|
Sign up to set email alerts
|

A multifractal detrended fluctuation description of Iranian rial–US dollar exchange rate

Abstract: The miltifractal properties and scaling behaviour of the exchange rate variations of the Iranian rial against the US dollar from a daily perspective is numerically investigated. For this purpose the multifractal detrended fluctuation analysis (MF-DFA) is used. Through multifractal analysis, the scaling exponents, generalized Hurst exponents, generalized fractal dimensions and singularity spectrum are derived. Moreover, contribution of two major sources of multifractality, that is, fat-tailed probability distri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(72 citation statements)
references
References 30 publications
0
71
1
Order By: Relevance
“…Similar phenomena are observed for exponential distributions in the partition function framework [51]. To understand the impact of the distribution, one can either remove the large positive and negative returns [52] or generate surrogate data having a Gaussian distribution while keeping the linear correlation of the original data [26,27,53]. In this Letter, we will systematically investigate these factors together with a new factor reflecting possible hidden patterns in the raw time series.…”
mentioning
confidence: 80%
“…Similar phenomena are observed for exponential distributions in the partition function framework [51]. To understand the impact of the distribution, one can either remove the large positive and negative returns [52] or generate surrogate data having a Gaussian distribution while keeping the linear correlation of the original data [26,27,53]. In this Letter, we will systematically investigate these factors together with a new factor reflecting possible hidden patterns in the raw time series.…”
mentioning
confidence: 80%
“…It should be noted that this parameter is identical to the width of the singularity spectrum f ðaÞ at f ¼ 0. A wider singularity spectrum indicates a richer multifractality (Norouzzadeh and Rahmani 2006a, b).…”
Section: Multifractal Detrended Fluctuation Analysis (Mfdfa)mentioning
confidence: 99%
“…Following that, Kantelhardt et al (2002) extended DFA into multifractal detrended fluctuation analysis (MFDFA) which enables the multifractal behavior of data to be detected, and by studying their shuffled and surrogate time series and comparing them with the results of the original series, the sources of multifractality can be investigated (Jafari et al 2007; Kimiagar et al 2009;Lim et al 2007;Niu et al 2008;Pedram and Jafari 2008;Telesca et al 2004). MFDFA has been used to study time series in geophysics (Kantelhardt et al 2003;Kavasseri and Nagarajan 2005;Koscielny-Bunde et al 2006), physiology (Dutta 2010;Makowiec et al 2006Makowiec et al , 2011, financial markets (Oswiecimka et al 2005;Yuan et al 2009), and the exchange rates of currencies (Norouzzadeh and Rahmani 2006a, b;Oh et al 2012;Wang et al 2011a, b). Multifractals describe the dynamic characteristics of systems more carefully and comprehensively, and characterize their properties both locally and globally.…”
Section: Introductionmentioning
confidence: 99%
“…Work on higher-frequency dat a [23,45] has found that the correlations are the most likely cause of mult ifract ality. Mixed result s have been found for foreign exchange rat es [46,51,52]. T hese varied result s imply t hat the main source of multifractality is dependent on the part iculars of each specific dat a set and t hat t here is no universal law.…”
Section: Source Of Scaling -Dist Ribut Ionmentioning
confidence: 99%